The reference genome and full-length transcriptome of pakchoi provide insights into cuticle formation and heat adaption. Issue 1 (26th May 2022) - Xu, Huimin; Wang, Chunhua; Shao, Guirong; Wu, Shasha; Liu, Peng; Cao, Ping; Jiang, Peng; Wang, Shubin; Zhu, Hong; Lin, Xiao; Tauqeer, Arfa; Lin, Yizhang; et al.
Abstract: Brassica rapa includes various vegetables with high economic value. Among them, green petiole type pakchoi ( B. rapa ssp. chinensis ) is one of the major vegetables grown in southern China. Compared with other B. rapa varieties, green petiole type pakchoi shows a higher level of heat resistance, which is partially derived from the rich epicuticular wax. Here we sequence a high-quality genome of green petiole type pakchoi, which has been widely used as the parent in breeding. Our results reveal that long terminal repeat retrotransposon insertion plays critical roles in promoting the genome expansion and transcriptional diversity of pakchoi genes through preferential insertions, particularly in cuticle biosynthetic genes. After whole-genome triplication, over-retained pakchoi genes escape stringent selection pressure, and among them a set of cuticle-related genes are retained. Using bulked-segregant analysis of a heat-resistant pakchoi cultivar, we identify a frame-shift deletion across the third exon and the subsequent intron of BrcCER1 in candidate regions . Using Nanopore long-read sequencing, we analyze the full-length transcriptome of two pakchoi cultivars with opposite sensitivity to high temperature. We find that the heat-resistant pakchoi cultivar can mitigate heat-caused leaf damage by activating an unfolded protein response, as well as by inhibiting chloroplast development and energy metabolism, which are presumably mediated by both transcriptional regulation and splicing factors. Our study provides valuable resources for Brassica functional genomics and breeding research, and deepens our understanding of plant stress resistance.